Causes of deaths of children with malignant tumors during hospitalization in a single center - Wang, Xiao-xia (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2010)
OBJECTIVE: To investigate the main causes of deaths and the influencing factors in children with malignant tumors in the hospital, explore the possible way to improve the treatment